2008
DOI: 10.2174/157339908783502361
|View full text |Cite
|
Sign up to set email alerts
|

Role of Inflammation in Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN) is the leading cause of end stage renal disease (ESRD). Although the pathogenesis of DN is multifactorial, local inflammatory stress may result from both the metabolic and hemodynamic derangements observed in DN. Inflammatory markers such as Interleukin-18 and Tumor Necrosis Factor (TNF)-alpha are increased in the serum of patients with diabetes and DN. This occurs at a very early stage of disease, and correlates with the degree of albuminuria. Recent data suggest that standard pharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(42 citation statements)
references
References 114 publications
2
39
0
1
Order By: Relevance
“…ICAM-1 is also present on the membranes of macrophages and lymphocytes [21]. ICAM-1 expression is increased in models of type 1 and 2 diabetes [22, 23] and can be induced by hyperglycemia, advanced glycosylation end products, oxidative stress, hyperlipidemia, hyperinsulinemia, and proinflammatory cytokines [24]. Like ICAM-1, MCP-1 is also increased significantly in DN, and expression levels correlate with the number of infiltrating interstitial macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…ICAM-1 is also present on the membranes of macrophages and lymphocytes [21]. ICAM-1 expression is increased in models of type 1 and 2 diabetes [22, 23] and can be induced by hyperglycemia, advanced glycosylation end products, oxidative stress, hyperlipidemia, hyperinsulinemia, and proinflammatory cytokines [24]. Like ICAM-1, MCP-1 is also increased significantly in DN, and expression levels correlate with the number of infiltrating interstitial macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…It is a novel biomarker that has been studied in detail in preclinical ischemia-reperfusion models and has been proved to play an important role in renal injury induced by acute ischemia-reperfusion in mice [6]. Numerous reports indicate that CKD patients have elevated serum or urine levels of IL-18 and its correlation with decreased renal function [79]. The aim of this research was to investigate the relationship of serum IL-18 levels with histopathological severity and renal prognosis in IgA nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…In diabetic patients with nephropathy, the levels of ICAM-1 and MCP-1 recruiting inflammatory immune cells of macrophages and granulocytes were elevated [14]. It was shown that MCP-1 appeared to be responsible for diabetic ECM accumulation and early inflammation in diabetic nephropathy pathogenesis [36].…”
Section: Discussionmentioning
confidence: 99%
“…There is accumulating evidence demonstrating that the diabetic nephropathy is closely related to mesangial inflammation [14]. The activation of NF-κB may play a pivotal role in the progression of renal injury by inflammatory factors in diabetes [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation